Dufour and Soret Effects on Unsteady MHD Free Convection and Mass Transfer Flow past a Vertical Porous Plate in a Porous Medium - Alam, M. S.; Rahman, M. M.; Samad, M. A. (Nonlinear Analysis: Modelling and Control, 2006)
The Dufour and Soret effects on unsteady MHD free convection and mass transfer flow past an infinite vertical porous plate embedded in a porous medium have been studied numerically. The non-linear partial differential equations, governing the problem under consideration, have been transformed by a similarity transformation into a system of ordinary differential equations, which is solved numerically by applying Nachtsheim-Swigert shooting iteration technique together with sixth order Runge-Kutta integration scheme. The effects of various parameters entering into the problem have been examined on the flow field for a hydrogen-air mixture as a non-chemical reacting fluid pair. Finally, the numerical values of local Nusselt number and local Sherwood number are also presented in tabular form.